The Application of Dynamic Relative Taxonomy to Study Professional Activity of Seniors in the Visegrad Group Regions in 2015-2019 - Grazyna DEHNEL; Marek OBREBALSKI; Marek WALESIAK (Communications of International Proceedings, 2020)
The purpose of the paper is to measure the scope and degree of differences in the level of seniors’ involvement in the labour market in the conditions of ageing population, covering the regions of Poland, Czechia, Slovakia and Hungary in 2015-2019. The involvement of senior citizens in the labour market is described using 4 variables: economic activity rate of the population aged 65 or over, employment at the age of 65-74 per 1000 total employment, employment rate of the population aged 65 or over, average number of weekly working hours in the main job of the population aged 65-74. The study was based on the data from Eurostat REGIO database. A dynamic relative taxonomy was adopted for the purpose of the study. The level of professional activity of seniors on the labour markets in the examined countries and regions shows an upward tendency. The seniors in Czechia presented a relatively high economic activity and clearly a lower one was recorded in the surveyed regions of Hungary and Slovakia. In Polish regions, however, significant interregional disparities were revealed in this respect. The results of the study also confirmed a significant correlation between the professional activity of seniors and the level of unemployment in a given region. A lower overall unemployment rate level in a region resulted in higher economic activity of seniors.
Keywords: silver economy; labour market; relative taxonomy; composite indicators